Epidemic behavior of the etiological agent of infectious coryza in layer chicken of Bangladesh with isolation, identification and pathogenicity study - Akter, Mir Rowshan; Khan, Md Shahidur Rahman; Rahman, Md Mostafizer; Kabir, S M Lutful; Khan, Md Abu Sayed (Asian Journal of Medical and Biological Research, 2016)
The present study was selected as infectious coryza is one of the major problems affecting poultry industry in the developing country like Bangladesh and the reports regarding infectious coryza are yet not be documented considering epidemiological investigation, proper isolation, identification and pathogenicity study. The epidemic behavior of the etiological agent of this disease were studied based on age, sex, breed, spatial and temporal differences after collection of samples suspected to be infected with infectious coryza in layer chicken of Bangladesh. The incidence rate of infectious coryza from field cases were recorded as per information received from farmers by using a structured questionnaire and also clinical signs and symptoms. The disease was very high in laying hen (18.38%) in Sylhet and growing birds (7.25%) in Khulna in comparing with prelaying stage (2.07%) also in Sylhet region of Bangladesh. In this study no significant differences was observed as their location variation except Sylhet (9.2%) in comparison with other areas (Rangpur 8.76%, Rajshahi -8.82%, Khulna - 8.83%, Dhaka 8.72 and Chittagong - 8.65% respectively) of Bangladesh but significant differences was observed as their age group. However, the incidence rate of this disease was found to be very high during winter (8.77%) in compare with summer (0.42%) season. Moreover, during investigation a total of 122 samples were collected from different areas of Bangladesh for the period of March 2011 to February 2014. The higher rate of incidence of A. paragallinarum was found in Sylhet (66.66%) and lowest in Dhaka (43.75%). The association of A. paragallinarum with different seasons revealed that higher incidence rate was found in winter season (52.26%) in comparison with summer season (1.85%). The suspected positive isolates were subjected to experimental pathogenicity study in natural host for there isolation of A. paragallinarum was done as per Kotch postulates. Asian J. Med. Biol. Res. March 2016, 2(1): 82-94